2011
DOI: 10.1111/j.1365-2702.2011.03778.x
|View full text |Cite
|
Sign up to set email alerts
|

Turkish nurses’ perceptions of spirituality and spiritual care

Abstract: These findings will enable nurses to consider the importance of spirituality and spiritual care. Grasping these concepts will enable nurses to become more sensitive in their daily practices of spiritual care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
91
1
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(123 citation statements)
references
References 31 publications
12
91
1
14
Order By: Relevance
“…In addition, are slightly higher than scores of the SSCRS of graduated nurses in other countries [16,24]. With regard to the SCCS and SAIL, the scores are slightly higher than those in nursing students in the Netherlands [2,25], but in general, differences in the scores are small.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, are slightly higher than scores of the SSCRS of graduated nurses in other countries [16,24]. With regard to the SCCS and SAIL, the scores are slightly higher than those in nursing students in the Netherlands [2,25], but in general, differences in the scores are small.…”
Section: Discussionmentioning
confidence: 88%
“…It is not clear whether these variables are predictors for nurses' attitudes towards spirituality and spiritual care. A survey among staff nurses in Turkey showed that nurses in pediatric and psychiatric departments reported higher sensitivity to spirituality and spiritual care compared to other departments [16]. Ruder, who investigated the nurses' perceptions of spiritual care [17], emphasizes explicitly that her study did not address the relationship between the sector of healthcare where the nurse worked and the spirituality.…”
Section: Introductionmentioning
confidence: 99%
“…The only study conducted in the ROI revealed similar findings [29]. With the exception of Turkish nurses in one study [38], most nurses see chaplains as a key resource for spiritual care [2,30]. Nonetheless, significant barriers exist to the provision of spiritual care or addressing of spiritual needs in healthcare practice.…”
Section: Introductionmentioning
confidence: 51%
“…Over the past 20 years, nurses' attitudes worldwide toward the provision of spiritual care have been surveyed extensively, revealing that most are positively disposed to providing spiritual support [2,[38][39][40]. Internationally, most nurses agree that they provide spiritual care as part of their nursing practice [29][30][31] although many are unprepared and may lack supporting education for the assessment or provision of such care [2,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation